Pengaruh Pendidikan Kesehatan Tentang Menarche Terhadap Tingkat Pengetahuan Remaja Putri di SD 66 Kota Bengkulu - Murwati Murwati; Sulastri Sulastri; Kartika Murya Ningrum; Tita Septi Handayani (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Rapid physical growth is not accompanied by mental maturity or psychological development. This is closely related to the age at which a child experiences menarche, which nowadays tends to occur earlier due to various influencing factors. Early menarche before a child reaches mental maturity, coupled with a lack of knowledge, evokes various psychological responses in girls experiencing menarche. Early menarche in girls also increases the risk of breast cancer, the incidence of abortion due to premarital sexual relations, and the transmission of sexually transmitted diseases. The aim of this study is to determine the effect of health education about menarche on the knowledge level of female adolescents at SD 66 in Bengkulu City. This research design uses a Pre-Experimental method with a One Group pre-post test design approach. The sample in this study consisted of 24 patients, using accidental sampling technique and the measurement tool used was a questionnaire sheet. Data analysis was conducted using the Paired t-test with a significance level of α 0.05. The univariate analysis results show that more than half of the respondents (54.2%) had sufficient knowledge before being given health education and more than half of the respondents (54.2%) had good knowledge after receiving health education. Bivariate analysis results indicate that health education on menarche has an effect on the level of knowledge of adolescent girls at SD 66 Bengkulu City with a p value of 0.000 ≤ 0.005. It is hoped that teachers at SD 66 in Bengkulu City can develop activity programs to support the improvement of reproductive health knowledge, particularly menarche, through health education, either by counselling or providing material outside lessons using engaging media such as audiovisual media like animated videos.